Ketamine, benzoate, and sarcosine for treating depression. (1st February 2023) - Cheng, Yu-Jung; Lin, Chieh-Hsin; Lane, Hsien-Yuan
Abstract: Studies have demonstrated the beneficial therapeutic effects of sarcosine, benzoate, and ketamine (including esketamine and arketamine) on depression. These drugs mainly act by modulating N-methyl-d -aspartate glutamate receptors (NMDARs) and reducing inflammation in the brain. Although ketamine, benzoate, and sarcosine act differently as the antagonists or coagonists of NMDARs, they all have demonstrated efficacy in animal models or human trials. In vitro and in vivo studies have indicated that sarcosine, benzoate, and ketamine exert their anti-inflammatory effects by inhibiting microglial activity. This review summarizes and compares the efficacy of the possible therapeutic mechanisms of sarcosine, benzoate, ketamine, esketamine, and arketamine. These compounds act as both NMDAR modulators and anti-inflammatory drugs and thus can be effective in the treatment of depression. This article is part of the Special Issue on 'Ketamine and its Metabolites'. Highlights: Ketamine, sodium benzoate, and sarcosine, which modulate NMDARs and reduce inflammation, can improve depressive symptoms. BDNF/TrkB/Akt/mTORC1 pathway contributes to antidepressant activity of ketamine, sodium benzoate, and sarcosine. Arketamine may provide a superior antidepressant effect through its anti-inflammatory activity.